Gastropoda Laut dan Chiton di Mikrohabitat Bangunan Pelindung Pantai Pelabuhan Krueng Geukueh Provinsi Aceh - Cut M. N. ‘Akla; Fitra Wira Hadinata; Nur Ikhsan; Welmar Olfan Basten Barat; Hendrik V. Ayhuan; Muhammad Hatta; Riri Ezraneti; Syahrial Syahrial (Universitas Diponegoro, 2022)
The study was carried out in March 2022 at 8 observation stations in the Krueng Geukueh Harbor coastal protection facility in Aceh Province, using the visual encounter method for 120 minutes. The Shannon-Weaver diversity index, Simpson dominance, and Shannon-Weaver uniformity were used to generate the gastropod ecology index, while PCA was used to examine dominance by specific species and CA was used to analyze similarities in species composition. The study's findings included 20 species, 7 families, and a group of chitons. Gastropods Littorina angulifera, Echinolittorina puncatata, Nerita chamaeleon, Mauritia arabica, Thais mancinella, Morula musiva and Herba corticata are classified as rare (relative frequency < 20%); Littorina undulata, Nerita planospira, Cypraea mauritiana and Chiton sp. classified as occasional (relative frequency 21 – 40%); Littorina brevicula and Echinolittorina placida are relatively common (relative frequency 41 – 60%); Nerita albicilla, Nerita costata, Tylothais virgata and Tenguella granulata are relatively common (relative frequency 61 – 80%); and Thais (Thalesa) aculeata, Trochus radiatus and Cellana radiata were found to be relatively abundant (relative frequency > 80%). The gastropod diversity and uniformity indices were both low (1.49 and 0.48, respectively), where as the dominance index was moderate (0.52). The PCA analysis revealed that the dominant gastropod species were C. mauritiana, M. arabica, and M. musiva, and the CA analysis revealed the establishment of three groups based on the species composition discovered as a result of human activities near the study site. Kajian dilakukan pada bulan Maret 2022 di 8 stasiun pengamatan pada bangunan pelindung pantai Pelabuhan Krueng Geukueh Provinsi Aceh menggunakan metode visual encounter selama 120 menit. Indeks ekologi gastropoda dihitung dengan indeks keanekaragaman Shannon-Weaver, dominansi Simpson dan keseragaman Shannon-Weaver, sedangkan dominansi oleh spesies tertentu dianalisis menggunakan PCA dan kesamaan komposisi spesiesnya dianalisis menggunakan CA. Hasil kajian mendapatkan 20 spesies dan 7 famili serta ditemukan juga kelompok chiton. Gastropoda Littorina angulifera, Echinolittorina puncatata, Nerita chamaeleon, Mauritia arabica, Thais mancinella, Morula musiva dan Herba corticata tergolong langka ditemukan (frekuensi relatif < 20%); Littorina undulata, Nerita planospira, Cypraea mauritiana dan Chiton sp. tergolong sesekali ditemukan (frekuensi relatif 21–40%); Littorina brevicula dan Echinolittorina placida tergolong sering ditemukan (frekuensi relatif 41–60%); Nerita albicilla, Nerita costata, Tylothais virgata dan Tenguella granulata tergolong umum ditemukan (frekuensi relatif 61–80%); serta Thais (Thalessa) aculeata, Trochus radiatus dan Cellana radiata tergolong melimpah ditemukan (frekuensi relatif >80%). Indeks keanekaragaman dan keseragaman gastropodanya tergolong rendah (1.49 dan 0.48), sedangkan indeks dominansinya tergolong sedang (0.52). Dari analisis PCA didapatkan spesies gastropoda yang mendominasi adalah C. mauritiana, M. arabica dan M. Musiva, kemudian hasil analisis CA memperlihatkan adanya pembentukan tiga kelompok berdasarkan